موقف النحاة المحدثين من آراء ابن مضاء في القضايا النحوية : دراسة تحليلية وموازنة - Mohd Fadhlillah Bin Abdul Patah (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2015)
The study examines the position of Ibn Madaʼ on traditional Arabic grammar which is highlighted in his book "ar-raddu ʻala an-nuḥah" which also contains different views from Arab traditional grammarians. In order to get balanced judgement on the issue, the researcher has to discover the views of Sawqi Dayf who was one of the editors who reviewed the book. Another objective of the study is to discover the position of modern grammarians on some aspects of syntax refutation by Ibn Madaʼ. An analytical and equilibration study is the appropriate method to highlight views from Ibn Madaʼ in order to extract the position of modern grammarians on the issue. The findings indicate that the modern grammarians have been influenced by Ibn Madaʼ's position on refuting some aspects of traditional Arabic grammar.